Atorvastatin in clinically-significant macular edema in diabetics with a normal lipid profile - Narang, S; Sood, S; Kaur, B; Singh, R; Malik, A; Kaur, J (Nepalese Journal of Ophthalmology, 2012)
Introduction: Lipid-lowering drugs preserve vision and reduce the risk of hard exudates in clinically-significant macular edema(CSME) in diabetics with an abnormal lipid profile. But their role in reducing CSME in diabetics with a normal lipid profile is not yet known. Objective: To evaluate the role of atorvastatin in CSME in diabetics with a normal lipid profile. Materials and methods: A prospective, randomized clinical trial was carried out. Thirty CSME patients with a normal lipid profile were randomly divided into Group A and B. Atorvastatin had been started in Group A four weeks prior to laser treatement. The main outcome measures were any improvement or deterioration in visual acuity and macular edema and hard exudates at six months follow-up. Statistics: Both the groups were compared using unpaired t test for quantitative parameters and chi-square test for qualitative parameters. A p value of < 0.05 was taken as significant. Results: Visual acuity, macular edema and hard exudates resolution was not significantly different in the two groups (P = 0.14, 0.62, 0.39 respectively). Conclusion: Atorvastatin does not affect treatment outcome in CSME with a normal lipid profile over a short term follow-up. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5846 NEPJOPH 2012; 4(1): 23-28